2011
DOI: 10.1073/pnas.1019559108
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic strategies to overcome crizotinib resistance in non-small cell lung cancers harboring the fusion oncogene EML4-ALK

Abstract: The echinoderm microtubule-associated protein-like 4 (EML4)-anaplastic lymphoma kinase (ALK) fusion oncogene represents a molecular target in a small subset of non-small cell lung cancers (NSCLCs). This fusion leads to constitutive ALK activation with potent transforming activity. In a pivotal phase 1 clinical trial, the ALK tyrosine kinase inhibitor (TKI) crizotinib (PF-02341066) demonstrated impressive antitumor activity in the majority of patients with NSCLC harboring ALK fusions. However, despite these rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
420
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(446 citation statements)
references
References 35 publications
17
420
4
2
Order By: Relevance
“…The gatekeeper L1196M was one of the first causes of Crizotinib resistance found in patients. A moderate AP26113 resistance was predicted in vitro (29,34,35); however, the IC 50 value is low enough to consider this mutation sensitive to AP26113. Because in SUP-M2AR500B cells both L1122V and L1196M were found, we hypothesize that the first is the mutation driving resistance, while the latter was selected at low doses and never counterselected, remaining as a passenger in the high-dose-resistant clone.…”
Section: Discussionmentioning
confidence: 99%
“…The gatekeeper L1196M was one of the first causes of Crizotinib resistance found in patients. A moderate AP26113 resistance was predicted in vitro (29,34,35); however, the IC 50 value is low enough to consider this mutation sensitive to AP26113. Because in SUP-M2AR500B cells both L1122V and L1196M were found, we hypothesize that the first is the mutation driving resistance, while the latter was selected at low doses and never counterselected, remaining as a passenger in the high-dose-resistant clone.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite these remarkable initial clinical responses, these cancers eventually developed resistance to crizotinib, usually within 1 year, thereby limiting the potential clinical benefit of this drug. Katayama et al 165 found that cells resistant to intermediate doses of crizotinib develop either amplification of the EML4-ALK gene or a gatekeeper mutation, L1196M, within the kinase domain. Sasaki et al 164 proposed two mechanisms of ALK TKI resistance based on evidence from a crizotinib-treated ALK-positive lung cancer patient and in a cell line generated from the resistant tumor.…”
Section: Eml4-alk Rearrangement: Driver Mutation Of Lung Cancermentioning
confidence: 99%
“…Hsp90 inhibitors induce the degradation of EML4-ALK variant 1 and regression in some EML4-ALK-positive tumor models (7,9,10). Furthermore, clinical efficacy of an Hsp90 inhibitor in EML4-ALK NSCLC has been confirmed (11), and clinical trials are ongoing.…”
mentioning
confidence: 98%
“…These fusions display potent transforming activity due to constitutive activation of the tyrosine kinase but confer addiction to the oncogene, and inhibition of the tyrosine kinase induces apoptosis in transformed cells (4,5). The ALK inhibitor crizotinib is a highly effective first-line therapy for NSCLC patients with EML4-ALK fusions, but because the acquirement of resistance is inevitable, often involving secondary mutations in the kinase portion of the fusion protein, additional therapeutic strategies must be identified (6,7).…”
mentioning
confidence: 99%